2005
DOI: 10.1007/s10517-005-0369-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Administration of Lead Nitrate to Pregnant Rats on the Lungs in Their Offspring

Abstract: Lead nitrate in a dose of 200 mg/kg was administered to female rats via a gartric tube on days 5 and 12 of pregnancy. The lungs of their offspring were examined on day 40 of life. We found a decrease in the ratio between the specific volumes of alveolar lumens and interalveolar septa and hypertrophy of lymphoid tissue in the bronchial wall (compared to the offspring of intact females). Chemiluminescent analysis revealed activation of lipid peroxidation and decrease in antioxidant antiradical activity of the lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
1
0
2
Order By: Relevance
“…Pb exposure during pregnancy is associated with a variety of neonatal perturbations, including low birth weight, delayed development and maturation, as well as later developing behavioural outcomes (Chang et al, 2012 ). Experimental studies demonstrated that administration of Pb to pregnant rats produced destructive changes in the brains of their offspring (Lebed'ko & Ryzhavskii, 2005 ; Ryzhavskii et al, 2008 ). Differential gender effects were also observed after in utero exposure to Pb throughout full gestation (Cory-slechta et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pb exposure during pregnancy is associated with a variety of neonatal perturbations, including low birth weight, delayed development and maturation, as well as later developing behavioural outcomes (Chang et al, 2012 ). Experimental studies demonstrated that administration of Pb to pregnant rats produced destructive changes in the brains of their offspring (Lebed'ko & Ryzhavskii, 2005 ; Ryzhavskii et al, 2008 ). Differential gender effects were also observed after in utero exposure to Pb throughout full gestation (Cory-slechta et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Данные клинические наблюдения о роли микроэлементов в формировании хронической патологии легких подтверждены экспериментальными исследованиями. На экспериментальной модели интоксикации свинцом [11] показаны особенности патоморфологических изменений в легких крыс, подвергнувшиеся антенатальному воздействию нитрата свинца (рис. 1).…”
Section: таблица 1 факторы риска развития блдunclassified
“…Виктория Р., 11 Представленное наблюдение иллюстрирует сложность дифференциальной диагностики хронического бронхолегочного заболевания у больного [7,18]. Отягощенный акушерский анамнез, недоношенность, на-личие СДР в периоде новорожденности, повторные обструктивные бронхиты, частые пневмонии с раннего возраста, неэффективность массивной неконтролируемой антибактериальной терапии, клинико-рентгенологические данные, предполагали наличие у ребенка порока развития легкого -гипоплазии нижних долей легкого, с рекомендациями оперативного лечения.…”
Section: частота встречаемости основных клинических симптомов у больнunclassified